Quality of Nursing Work Life (QNWL) in Indonesia: Scoping Review - Agusto, Nyoman Wigo; Leo, Kadek Agus; Septianita, Nisa EKa (GLOBAL HEALTH SCIENCE GROUP, 2024)
QNWL must continue to be considered to improve the welfare of nurses, especially during the COVID-19 pandemic. The purpose of this study was to determine the description and factors associated with QNWL in Indonesia. This research is a Scoping Review, namely the identification of articles through 3 databases including Google Scholer, Science Direct and Pubmed with the keywords